1998
DOI: 10.1016/s0092-8674(00)81707-9
|View full text |Cite
|
Sign up to set email alerts
|

Fab1p PtdIns(3)P 5-Kinase Function Essential for Protein Sorting in the Multivesicular Body

Abstract: Sorting of signal-transducing cell surface receptors within multivesicular bodies (MVBs) is required for their rapid down-regulation and degradation within lysosomes. Yeast mutants defective in late stages of transport to the vacuole/lysosome accumulate MVBs. We demonstrate that the membrane glycoprotein carboxypeptidase S and the G protein-coupled receptor Ste2p are targeted into the vacuole lumen, and this process requires a subset of VPS gene products essential for normal endosome function. The PtdIns(3)P 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
702
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 619 publications
(740 citation statements)
references
References 50 publications
32
702
0
6
Order By: Relevance
“…These MVBs may thus act as a separate compartment and/or transport intermediates between the Golgi apparatus and the MVT ( Figure 5H). Collectively, these studies suggest that the MVBs and MVT are post-Golgi compartments and that they have the characteristic internal structure of late endosomes or lysosomes (Gruenberg and Maxfield, 1995;Odorizzi et al, 1998).…”
Section: Tubule Compartment Is a Multivesicular Post-golgi Compartmentmentioning
confidence: 84%
See 2 more Smart Citations
“…These MVBs may thus act as a separate compartment and/or transport intermediates between the Golgi apparatus and the MVT ( Figure 5H). Collectively, these studies suggest that the MVBs and MVT are post-Golgi compartments and that they have the characteristic internal structure of late endosomes or lysosomes (Gruenberg and Maxfield, 1995;Odorizzi et al, 1998).…”
Section: Tubule Compartment Is a Multivesicular Post-golgi Compartmentmentioning
confidence: 84%
“…We now show that the MVT is a terminal lysosome compartment based on the following lines of evidence. First, the EM ultrastructural studies indicate that the MVT is a post-Golgi compartment with the same internal structure as late endosomes/lysosomes in other eukaryotic cells (Kobayashi et al, 1998;Odorizzi et al, 1998). Second, the MVT is labeled in a time-and temperature-dependent manner with the well-defined endocytic marker FM 4-64.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate from its activity as an Rsp5 client, trafficking of Cps1 from the cell membrane to the vacuole has been well characterized and Cps1 is frequently used as a model cargo to study protein trafficking through MVBs (Odorizzi et al ., 1998). Using a quantitative, luciferase‐based assay to search for defects in MVB formation and sorting (Nickerson et al ., 2012; Nickerson & Merz, 2015), we observed that the original chr5 disome has a Cps1 trafficking defect that is ameliorated by the deletion of BUL1 or the bul1 Q146K allele (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the classical endosome pathway, maturation involves Rab5 on early endosomes (EEs) and its exchange for Rab7 on late endosomes (LEs) and lysosomes (LYs) 5, 6. In addition, there is conversion of phosphatidylinositol 3‐phosphate (PtdIns(3)P) to PtdIns(3,5)P 2 , and progressive luminal acidification 7, 8, 9, 10, 11. As virus penetration and uncoating relies on the environment within maturing endosomes, it is perhaps no surprise that for many viruses, infection depends on factors involved in the maturation process 12, 13, 14.…”
mentioning
confidence: 99%